Executive Function Performance and Change in Aging is Predicted by Apolipoprotein E, Intensified by Catechol-O-methyltransferase and Brain-derived neurotrophic factor, and Moderated by Age and Lifestyle - Sapkota, Shraddha (Neurobiol Aging, 2017)
Recent studies have reported several genetic, health, and aging interaction effects in predicting cognitive performance and change. We used an accelerated longitudinal design to examine interactions among genetic, lifestyle, and aging for executive function (EF) in non-demented older adults (n=634; age range=53–95 years). The polymorphisms were Apolipoprotein E (APOE), Catechol-O-methyl transferase (COMT), and Brain-derived neurotrophic factor (BDNF). We tested (a) independent and additive effects of APOE, COMT, and BDNF and (b) APOE effect modification for COMT+ BDNF, on EF performance and 9-year change as separated by age and lifestyle activities. First, APOE ε4+ carriers had poorer EF performance and steeper 9-year decline. Second, APOE ε4+ carriers with (a) BDNF Met/Met genotype and (b) increasing allelic risk in the COMT+ BDNF risk panel had poorer EF performance; these effects were moderated by lifestyle activities (composite of everyday social, physical, cognitive activities). Examining APOE effect modification for COMT+ BDNF risk panel effects with other moderating factors may help identify complex neurobiological and genetic underpinnings of polygenic phenotypes such as EF in aging.